Impact of transformational leadership, happiness management, and work stress on turnover intention. - Martínez-Arvizu, Orlando Josué (2025)
In the context of ongoing labour transformation and increasing talent turnover, understanding the factors influencing employee retention has become a strategic priority for modern organisations. This study analyses the effect of transformational leadership on turnover intention, incorporating happiness management and work-related stress as mediating variables. Additionally, it explores potential differences between Mexico's public and private sectors. A quantitative, non-experimental, and cross-sectional design was employed, using a structured questionnaire administered to a sample of 414 employees from various institutions. Data were analysed through Covariance-Based Structural Equation Modelling (CB-SEM) and multigroup analysis. The results indicate that transformational leadership positively influences happiness management, reducing stress and turnover intention. Although work-related stress increased turnover intention, its mediating effect was not statistically significant. Sectoral differences were also observed: in the private sector, transformational leadership acted as a buffer against stress, whereas in the public sector, happiness management played a stronger role in reducing turnover. The proposed model contributes to the advancement of Social Exchange Theory by incorporating emotional mechanisms as key explanatory factors for employee retention. The findings offer valuable insights for developing human-centred organisational policies tailored to sector-specific dynamics and aligned with the Sustainable Development Goals related to decent work and emotional wellbeing.